Exploring Logical-Mathematical Intelligence and Hyperactivity in School-Level Student: A Case Study of Cognitive Profiles and Academic Performance - Dahal, Rudra Nath (BARUN Journal, 2026)
This case study examines the academic and developmental profile of Siddhartha Himali, a mathematically gifted secondary-level student from Sankhuwasabha District, Nepal. The study explores his personal background, academic trajectory, behavioural characteristics, and exceptional aptitude in logical-mathematical reasoning. Siddhartha demonstrates advanced mastery of higher secondary mathematics while still in Grade 9, reflecting strong intrinsic motivation, self-directed learning habits, and high-level abstract thinking skills. His learning environment, characterized by parental support and academic freedom, has played a significant role in nurturing his intellectual growth. However, the study also identifies key developmental challenges, including limited social engagement, reduced interest in non-mathematical subjects, and potential emotional concerns associated with intense cognitive focus. These findings highlight the need for a balanced educational approach that supports both cognitive acceleration and socio-emotional development. The case emphasizes differentiated instruction, mentorship opportunities, interdisciplinary integration, emotional intelligence development, and collaborative parental-teacher support as essential strategies for holistic growth. Overall, the study underscores the importance of structured yet flexible support systems to sustain gifted learners’ talents while ensuring well-rounded personality development and long-term well-being.